Juri Pemilihan Bujang Dara Riau 2023 - Yani, Fitri; Putra, Rizaldi; Purnama, Intan; Suharti, Suharti; Rezfajri, Maulana; Aprila, Bord Nandre; Saputra, Hidayat; Rusilawati, Ermina (JUDIKAT: Jurnal Pengabdian Kepada Masyarakat, 2023)
This community service activity was organized by the Riau Provincial Tourism Office in order to improve the development of the tourism sector through the Riau Bujang Dara Selection event. The purpose of the Bujang Dara Riau Election is to find young people who have potential and are expected to become role models for other young people. The competition method is that participants are sons and daughters of the region who come from 12 regencies and cities in Riau Province. Furthermore, it is selected by the Regency and City Tourism Office respectively so that one pair of Bujang Dara winners will be selected as finalists and represent the area to continue to the Provincial Level Bujang Dara election. Furthermore, the judges assessed the cultural knowledge, traditional knowledge, intellectual knowledge, public speaking, character, education and insight of the finalists.